Brazil's urban land and housing markets: How well are they working? - David E. Dowall (University of California, Institute of Urban and Regional Development (IURD), 2006)
This paper uses a macro, national-level perspective to assess urban land and housing market outcomes across Brazil. It is based on available empirical data from IBGE, field studies, the Fundaç\~ao Jo\~ao Pinheiro, and other sources. The paper starts by posing and answering the following questions: What are the characteristics of well-functioning urban land and housing markets? How well are Brazils urban land and housing markets performing relative to other countries? It then proceeds to provide an assessment of urban land and housing market outcomes in Brazilian cities. The paper concludes by exploring a range of opportunities for enhancing urban land and housing market outcomes.
Keywords: 330